Perancangan Ulang Tampilan Antarmuka Website Tempat Wisata Setu Babakan - Amta, Amta; Krishnasari, Erneza Dewi; Putra, Damar Rangga (Universitas Trilogi, 2019)
The development of information technology has penetrated the world of tourism, one of which is the need for websites as a medium for finding tourist attractions and planning trips. One tourist site that has an official website is the Betawi Cultural Village Setu Babakan, a tourist place where visitors can find things related to Betawi culture such as traditional houses, arts, and food. based on a User Acceptence Test study for visitors to Setu Babakan, the website has not been maximized in providing detailed information related to tourist attractions, and does not yet represent the Betawi culture. For this reason, a website redesign is required using the usecase diagram method. The results of this study are in the form of usecase diagrams, wireframes and website user interfaces.